A Meta‐Analysis of the Association Between Appraisals of Trauma and Posttraumatic Stress in Children and Adolescents. Issue 1 (19th January 2017) - Mitchell, Ryan; Brennan, Kate; Curran, David; Hanna, Donncha; Dyer, Kevin F. W.
Abstract : Cognitive models of posttraumatic stress disorder (PTSD) place an emphasis on the role of negative appraisals of traumatic events. It is suggested that the way in which the event is appraised determines the extent to which posttraumatic stress symptoms will be experienced. Therefore, a strong relationship between trauma appraisals and symptoms of PTSD might be expected. However, this relationship is not as firmly established in the child and adolescent literature. A systematic literature review of this relationship returned 467 publications, of which 11 met full eligibility criteria. A random effects meta‐analysis revealed a large effect size for the relationship between appraisals and PTSD symptoms in children and adolescents, r = .63, 95% CI [.58, .68], Z = 17.32, p < .001, with significant heterogeneity present. A sensitivity analysis suggested that this relationship was not contingent on 1 specific measure of appraisals. Results were consistent with the cognitive behavioral theory of PTSD, demonstrating that appraisals of trauma are strongly related to posttraumatic stress in children and adolescents. However, this relationship was not observed in a sample of 4‐ to 6‐year‐olds, indicating that further research is required to explicate cognitive processing of trauma in very young children.